Evaluation of Parenting Patterns with the Application of Stoicism Philosophy on the Achievement of Cadets Softskill Competency - Egbert Edward Djajasasana (Cetta: Jurnal Ilmu Pendidikan, 2023)
The parenting pattern of all Indonesian MET solely aimed at the forming of soft skill competency as described on the guidance of the parenting pattern issued by the Ministry of Transportation of Indonesia. This competency must align with the curriculum and be embedded through the concept of boarding school. The soft skill competency which is integrity, teamwork, communication through interpersonal, adaptation, initiative and work ethic must be achieved within the period while the trainee study on the MET. This research scope is to find the result of the influence of the stoicism philosophy in one of the soft skill competencies which is work ethic. The method used in this research is participatory research of actions with qualitative descriptive analysis. The subjects used were 71 students of the Advance Diploma Program in Nautical batch 66. The results showed that by implementing stoicism philosophy such as live accordance to nature, controlling interpretation and perception, dichotomy of control and mental strength through action such as mistake point and reward point has been proved effective to achieve soft-skill competency which is work ethics (44.4%) and adaptation (38.1%).